Confirmation and detection of novel acetolactate synthase- and protoporphyrinogen oxidase–inhibiting herbicide-resistant redroot pigweed (Amaranthus retroflexus) populations in North Carolina. Issue 2 (14th February 2023) - Jones, Eric A. L.; Andres, Ryan J.; Dunne, Jeffrey C.; Leon, Ramon G.; Everman, Wesley J.
Abstract: Complaints of control failures with acetolactate synthase (ALS)- and protoporphyrinogen oxidase (PPO)-inhibiting herbicides on redroot pigweed ( Amaranthus retroflexus L.) were reported in conventional soybean [ Glycine max (L.) Merr.] fields in North Carolina. Greenhouse dose–response assays confirmed that the Camden County and Pasquotank County populations were less sensitive to ALS- and PPO-inhibiting herbicides compared with susceptible A. retroflexus populations, suggesting the evolution of resistance to these herbicides. Sanger sequencing of target genes determined the Camden County population carried a Trp-574-Leu mutation in the ALS gene and an Arg-98-Gly mutation in the PPX2 gene, while the Pasquotank County population carried a His-197-Pro mutation in the ALS gene (first documentation of the mutation in the Amaranthus genus), but no mutation was detected in the PPX2 gene. Single-nucleotide polymorphism (SNP) genotyping assays were developed to enable efficient screening of future control failures in order to limit the spread of these herbicide-resistant populations. In addition, preliminary testing of these assays revealed the three mutations were ubiquitous in the respective populations. These two populations represent the first confirmed cases of PPO-inhibiting herbicide-resistant A. retroflexus in the United States, as well as the first confirmed cases of this particular herbicide-resistance profile in A. retroflexus inhabiting North America. While no mutation was found in the PPX2 gene of the Pasquotank County population, we suggest that this population has evolved resistance to PPO-inhibiting herbicides, but the mechanism of resistance is to be determined.